Kingdom come : the amillennial alternative - Storms, C. Samuel, 1951- (Fearn, Scotland : Mentor, 2013)
The second coming of Christ is a matter of sharp disagreement amongst Christians. Many hold to premillennialism: that Christ's return will be followed by 1,000 years before the final judgement. However, premillennialism is not the only option for Christians. In this new book, Sam Storms provides a biblical rationale for amillennialism; the belief that 1,000 years mentioned in the book of Revelation is symbolic with the emphasis being the King and his Kingdom. --from publisher description
Includes bibliographical references and index
Keywords: Millennialism; Eschatology -- Biblical teaching